PENDAMPINGAN PEMBENTUKAN EMBRIO KOPERASI PETANI KOPI DI DESA SAJANG - Pancawati, Ni Luh Putu Anom; Sudarma, I Made; Ariana, I Made Putu Dwi; Anggara, I Gusti Lanang Oka Dwitya; Purwantari, I Gusti Ayu (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
As one of the best coffee producers in West Nusa Tenggara, Sajang Village has tremendous potential to be developed in terms of economy and tourism. The village, located at the foot of Mount Rinjani, can produce coffee that attracts coffee lovers. Most villagers are coffee farmers who depend on their livelihood to improve their welfare. Some of the challenges faced include coffee processing still using traditional systems. However, some others have implemented conventional methods, selling crops that are still below the standard price and marketing networks that are still minimal. To provide better economic benefits, the community as coffee farmers want a community that can accommodate their aspirations and desires and be able to answer the problems faced to get solutions. By assisting with lecture and discussion methods with several coffee farming community members accompanied by local community leaders, it was agreed to form the embryo of the Sajang coffee farmer cooperative that houses the coffee farming community as its members. The presence of the community can build local economic independence that provides a better domino effect for their lives. So, through this service, assistance in forming a coffee farmer cooperative embryo becomes a bridge to getting answers to the problems and challenges coffee farmers face in Sajang Village.